Pandangan Mahasiswa Terhadap Dinamika Polemik Pemilihan Umum (Pemilu) Tahun 2024 - Mohamad Feby; Arum Mustika Farida (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
This research aims to find out the opinions of Untirta students regarding the dynamic situation of the polemics in the 2024 general election. The problems discussed in this case are regarding students' understanding of the dynamics of the polemics in the 2024 elections as well as the role of students in students' efforts to improve, supervise and supervise each election. , the role of students is very important in guarding and supervising the election process. In the method of selecting several journals as a literature review, there is an interview technique carried out by interviewing several sources regarding their views as students in looking at the polemic dynamics that occurred in the 2024 election. The results of this research are that regarding the polemic dynamics that occurred in the 2024 election, students are of the view that there are still There is fraud occurring in the 2024 election, as in previous elections, therefore students play an important role in overseeing and supervising each election as a form of effort to improve and maintain the principles of democracy.